Конструктивно-географічні та соціально-економічні фактори функціонування Волинського регіонального агропродовольчого ринку - Потапова, Алла Геннадіївна; Potapova, Alla H. (Вінницький державний педагогічний університет імені Михайла Коцюбинського, 2008)
Modern social and economical processes in Volyn region influence on functioning of regional agricultural market in two ways. In one side, great supply on foodstuffs, low level of population’s employment, enough transport and communication developing with nature-ecological factors induce to further agrobusiness development. In another side, insufficient financing agrobusiness, “non-prestige” of agricultural activity and imperfect agrarian reforms are limited factors of regional agricultural market functioning
Keywords: регіональний агропродовольчий ринок